TRIBOLOGICAL COATINGS SELECTION AND DEVELOPMENT - Lopata, Larisa A.; Brusilo, Yuri V. (Proceedings of National Aviation University, 2010)
The strategy and methodology for selecting of optimal surface treatment for a given tribological application are the main objectives of study. The scheme of development of operation technology of surface treatment and coating deposition is proposed.